Advanced Test of Attention in Children with Attention-Deficit/Hyperactivity Disorder in Japan for Evaluation of Methylphenidate and Atomoxetine Effects - Fujioka, Toru (Clin Psychopharmacol Neurosci, 2016)
OBJECTIVE: This study was conducted to validate the Advanced Test of Attention (ATA) of the visual attention version of Japanese children with attention deficit/hyperactivity disorder (ADHD) and to evaluate the efficacy of methylphenidate (OROS-MPH) and atomoxetine medications. METHODS: To assess pharmacotherapy efficacy, the visual version of ATA was administered to 42 children with ADHD. Results were assessed using discriminant analysis, ANOVA for indices of ATA before and after medication treatment, and correlation analysis between the improvement of indices of ATA and clinical symptoms during medication treatment. RESULTS: Discriminant analysis showed that 69.0% of ADHD children were assigned correctly. The T score of commission errors increased as the trial progressed on the medication-off condition. T scores of commission errors and standard deviation of response times on medication-on condition were low compared to the medication-off condition. A few significant correlations were found between the improvements of indices of ATA and ADHD-Rating Scale (RS) during treatment. CONCLUSION: The performance of the visual version of ATA on medication-off condition reflected the features of ADHD. Furthermore, the medication treatment effects were confirmed sufficiently. In addition, results suggest that indices of ATA reflected aspects of ADHD symptoms that are difficult to elucidate for ADHD-RS. For assessing symptoms and effects of medical treatment in children with ADHD, ATA might be a useful assessment tool.